The environmental drag on long- term economic performance: Evidence from Norway - Annegrete Bruvoll; Solveig Glomsrød; Haakon Vennemo (Statistics Norway, Research Department, 1995)
The environmental drag is the cost to society of environmental constraints. This paper estimates the long-run environmental drag on the Norwegian economy. We employ a model called DREAM (dynamic resource / environmental applied model). This is an applied general equilibrium model extended to include important environmental linkages. After having explained the structure of our model, the paper presents macroeconomic effects, and impacts on growth and welfare of environmental constraints. To check robustness we perform a number of sensitivity analyses. Most of our results are remarkably robust to alternative assumptions. Contrary to widespread opinion, a low discount rate increases the environmental drag on welfare. Reducing the rate of technological progress will have similar effects.
Keywords: D58; O41; Q29; Q39; 330; Environmental drag; dynamic CGE model; Norway.